Difusi Norma Kerja Sama Keamanan ASEAN Melawan Perdagangan Manusia - Pradityo, Rahmadanu; Fajrilla Sidiq, Mabda Haerunnisa; Kurniawan, Yandry (Andalas Institute of International Studies UNAND, 2021)
The United Nations (UN) ratified the United Nations Convention against Transnational Organized Crime (UNCTOC) in 2000 as the norm for international security cooperation in addressing transnational crimes that threaten the global security. Transnational crimes include human trafficking that involves a wide range of criminal organizations and networks. Therefore, ASEAN also refers to UNCTOC and the Trafficking in Person (TIP) Protocol in overcoming transnational crimes, especially the fight against human trafficking. This paper proposes questions ASEAN's attitude to not adopt all UNCTOC norms and Trafficking in Person Protocol in the ASEAN Convention on Trafficking in Person, Especially Women and Children (ACTIP). This paper uses qualitative research methods and norm diffusion theory as the analytical framework. This study found that ASEAN did not fully adopt external norms because there were parts that were not in accordance with ASEAN's internal norms, so that ASEAN made adjustments between external norms and ASEAN internal norms in the formation of ACTIP which referred to ASEAN's cognitive priors, so that ACTIP became the security cooperation norms with human rights element.